2023
DOI: 10.3390/cells12242789
|View full text |Cite
|
Sign up to set email alerts
|

Human Probiotic Lactobacillus paracasei-Derived Extracellular Vesicles Improve Tumor Necrosis Factor-α-Induced Inflammatory Phenotypes in Human Skin

Kwang-Soo Lee,
Yunsik Kim,
Jin Hee Lee
et al.

Abstract: Lactic acid bacteria (LAB), a probiotic, provide various health benefits. We recently isolated a new Lactobacillus paracasei strain with strong anti-inflammatory effects under lipopolysaccharide-induced conditions and proposed a new mode of action—augmenting the endoplasmic reticulum stress pathway for anti-inflammatory functions in host cells. The beneficial effects of the L. paracasei strains on the skin have been described; however, the effects of L. paracasei-derived extracellular vesicles (LpEVs) on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…The promising versatility and efficacy of probiotic EVs suggest a bright future for this novel biomedical approach . Recent studies have indicated that EVs secreted by a variety of Lactobacillus species can promote the recovery of inflammatory bowel disease in the animal model. , The experimental oral administration of LP-UJS-EVs directly demonstrates its therapeutic potential in promoting intestinal barrier restoration and alleviating UC. This efficacy is substantiated by a range of outcomes, including the notable increase in mouse body weight, reduction in DAI, restoration of colorectal length, structural mending of the intestines, mitigation of inflammatory infiltration, and elevation in the expression levels of intestinal-related functional proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The promising versatility and efficacy of probiotic EVs suggest a bright future for this novel biomedical approach . Recent studies have indicated that EVs secreted by a variety of Lactobacillus species can promote the recovery of inflammatory bowel disease in the animal model. , The experimental oral administration of LP-UJS-EVs directly demonstrates its therapeutic potential in promoting intestinal barrier restoration and alleviating UC. This efficacy is substantiated by a range of outcomes, including the notable increase in mouse body weight, reduction in DAI, restoration of colorectal length, structural mending of the intestines, mitigation of inflammatory infiltration, and elevation in the expression levels of intestinal-related functional proteins.…”
Section: Discussionmentioning
confidence: 99%